2018
DOI: 10.1111/acer.13852
|View full text |Cite
|
Sign up to set email alerts
|

What Predicts What? Self‐Reported and Behavioral Impulsivity and High‐Risk Patterns of Alcohol Use in Spanish Early Adolescents: A 2‐Year Longitudinal Study

Abstract: Within-person levels of self-reported impulsivity and sensation seeking significantly predicted further heavy drinking from as early as 13 years old, whereas behavioral measures were not predictive. In our study, neither IE nor ARP predicted prospective changes in impulsivity. Further studies should address additional specific relationships between facets of impulsivity and specific outcomes of heavy drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Up to now, a small number of longitudinal studies have reported small to medium predictive associations between steeper delay discounting and an increased likelihood of smoking initiation (for an overview, see Barlow et al 2017 ) or later alcohol involvement in healthy adolescents (Fernie et al 2013 ). However, there was only weak evidence that impulsive decision-making predicts the alcohol quantity-frequency index (QFI) 1 year later (Bernhardt et al 2017 ) or alcohol use, intoxication, and problems 2 years later (Fernández-Artamendi et al 2018 ). Concerning longitudinal evidence, three research needs are addressed in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, a small number of longitudinal studies have reported small to medium predictive associations between steeper delay discounting and an increased likelihood of smoking initiation (for an overview, see Barlow et al 2017 ) or later alcohol involvement in healthy adolescents (Fernie et al 2013 ). However, there was only weak evidence that impulsive decision-making predicts the alcohol quantity-frequency index (QFI) 1 year later (Bernhardt et al 2017 ) or alcohol use, intoxication, and problems 2 years later (Fernández-Artamendi et al 2018 ). Concerning longitudinal evidence, three research needs are addressed in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the coexistence of alcohol problems and bulimic symptoms were found in the present study, as these were moderately correlated with each other. In addition to this co-occurrence of disorders, sensation seeking is likely to be an antecedent to at least alcohol problems [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent cross-sectional studies conducted in student or mostly student populations identified a positive association between sensation seeking, bulimic symptoms, and alcohol problems [17,18]. As sensation-seeking seems to be an antecedent to alcohol problems [19,20], alcohol problems could mediate the effects of sensation seeking on bulimic symptoms, but further studies are needed to clarify the longitudinal aspects and relevance in the general population. We know also that individuals with diagnosed bulimia nervosa and other eating disorders report more alcohol problems than do individuals without eating disorders [21].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, evidence about the effects of alcohol use on DD is rare. To our knowledge, there are two longitudinal studies reporting no effect of adolescent alcohol use on future DD (Fernández-Artamendi et al, 2018;Fernie et al, 2013). These studies investigated participants over a 2-year period.…”
Section: Introductionmentioning
confidence: 99%